Recent advances in targeting the cGAS–STING pathway for immunotherapy in orthopedic diseases - Wu, Feipeng; Hui, Shan; Li, Dapeng; Pan, Guoqing; Zhang, Wenchao (Frontiers in Immunology, 2025)
With increasing evidence highlighting the role of immune dysregulation in orthopedic diseases such as osteoarthritis, osteoporosis, intervertebral disc degeneration, delayed fracture healing, and bone tumors, the cyclic GMP-AMP synthase–stimulator of interferon genes (cGAS–STING) pathway has emerged as a central mediator of innate immune sensing and sterile inflammation. This review summarizes the core mechanisms of cGAS-STING activation and its involvement in regulating inflammatory responses, bone remodeling, cell death, and immune cell polarization in musculoskeletal tissues. In particular, we discuss recent findings on how aberrant cGAS-STING signaling contributes not only to chronic inflammatory bone loss but also to the tumor immune microenvironment in primary bone cancers and bone metastases. Furthermore, we highlight the therapeutic prospects of targeting this pathway using agonists or inhibitors, which show promise for novel immunomodulatory approaches in the treatment of orthopedic diseases, including skeletal malignancies.